2019
DOI: 10.4236/health.2019.117069
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Completeness in the Filling of Laboratory Request Forms Submitted to the Haematology Laboratory at a Tertiary Hospital in Kenya

Abstract: Background information: The laboratory request form is a communication link between the clinicians and the laboratory staff. It contains demographic details of the patient including full names, age and gender; the test required; location of the patient; date and time of request among other details. Incomplete and inaccurate filling of the request forms may cause errors which can impact on the quality of the patient care. Methodology: The study was a descriptive cross sectional where 289 laboratory request form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
4
2
3
Order By: Relevance
“…This finding was consistent with the study conducted in Hawassa, Ethiopia 27 (39.4%), but lower than a study conducted in Gondar, Ethiopia 20 with an overall incompleteness of 49.9%. In contrast, the current finding was much higher than studies in Nigeria, 28 Kenya 29 and Uganda 30 with an incompleteness rate of 14.3%, 22.7% and 17.9%, respectively. This disparity may be due to variation in quality indicators, study designs, study periods, awareness and experience of clinicians on the value of patient information.…”
Section: Discussioncontrasting
confidence: 95%
“…This finding was consistent with the study conducted in Hawassa, Ethiopia 27 (39.4%), but lower than a study conducted in Gondar, Ethiopia 20 with an overall incompleteness of 49.9%. In contrast, the current finding was much higher than studies in Nigeria, 28 Kenya 29 and Uganda 30 with an incompleteness rate of 14.3%, 22.7% and 17.9%, respectively. This disparity may be due to variation in quality indicators, study designs, study periods, awareness and experience of clinicians on the value of patient information.…”
Section: Discussioncontrasting
confidence: 95%
“…The name of the patient in this study was the only parameter that presents in all the laboratory requests and reports forms. This is proportion is similar to the findings of other studies [15,17,[19][20][21] that the name of the patient was fully completed. This might be due to the fact that patients' names were as simple as it appears to be first in many requests and report format [6] and may also be due to rejected at the reception of any request form that has no patients' name.…”
Section: Discussionsupporting
confidence: 91%
“…Other study needed to identify the reasons for the inadequate filling of the laboratory request forms by the clinicians and result form by laboratory personnel should be carried out. [15,19] and Kenya 14.9% [20]. However, it was comparable with a report from North India 98% [17].…”
Section: Recommendationsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are corroborated by several other local and international studies. [7], [17][18][19][20] Apart from the patients' names, tests requested and nature of samples which were present on all the forms examined, almost all the other major parameters were frequently omitted at one time or the other in the course of the study, a reflection of what is regularly obtainable. This is similar to what other studies have reported, and it is understandably so.…”
Section: Discussionmentioning
confidence: 99%